Possible functional scaffolds for periodontal regeneration - Hidetoshi Shimauchi; Eiji Nemoto; Hiroshi Ishihata; Masatsugu Shimomura (Elsevier, 2013)
Periodontal diseases are the most prevalent infectious diseases with the irreversible loss of tooth supporting apparatus. To reestablish the stable health of periodontal tissues after healing, the concept of regenerative surgical procedures has been developed over the past three decades, including various grafting materials, guided tissue regeneration (GTR), and the use of enamel matrix derivatives (EMD) in a clinical setting. More recently, tissue engineering strategies have also been applied and developed for periodontal regeneration: (1) stem cell therapies; (2) recombinant human growth factor therapies; (3) combined use of cell and growth factors with matrix-based scaffolds. However, the complete and predictable reconstruction of healthy periodontal tissues still remains a challenging field. To overcome therapeutic limitations and develop stem cell-based strategies, it is necessary to optimize cell-scaffold combinations by understanding the cellular events during periodontal wound healing and regeneration. We reviewed: (1) the current status and strategies for periodontal regeneration; (2) a possible biomaterial design for the scaffold used in periodontal tissue engineering; (3) a possible interaction between scaffold materials and periodontal tissue cells.